RCS 2023
DOI: 10.31876/rcs.v29i3.40694
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors associated with lifestyle in Venezuelan university students

Abstract: College brings emotional, cognitive, and physiological changes in students, along with academic stress that can affect their lifestyle and health. The present study aimed to determine the influence of psychological factors associated with the lifestyles of Venezuelan higher education students. This research was a quantitative, non-experimental study that analyzed the relationship between lifestyles, life satisfaction and sense of coherence in 843 students of the Universidad Centrooccidental Lisandro Alvarado i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
1
0
2
Order By: Relevance
“…En la etapa universitaria ocurren cambios significativos a nivel social, psicológico y educativos, se asumen nuevas responsabilidades y se toma un papel más activo en la toma de decisiones relacionados con ellos mismos (2,25,26). Por tanto, resulta importante determinar las conductas de salud de los estudiantes en pro de desarrollar y proteger su salud, modificar los hábitos inadecuados y asegurar la continuación de hábitos más saludables (27).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En la etapa universitaria ocurren cambios significativos a nivel social, psicológico y educativos, se asumen nuevas responsabilidades y se toma un papel más activo en la toma de decisiones relacionados con ellos mismos (2,25,26). Por tanto, resulta importante determinar las conductas de salud de los estudiantes en pro de desarrollar y proteger su salud, modificar los hábitos inadecuados y asegurar la continuación de hábitos más saludables (27).…”
Section: Discussionunclassified
“…Las conductas de salud hacen referencia al conjunto de acciones y comportamientos que ejecuta una persona con la intención de mantener, mejorar o recuperar su estado de salud y bienestar físico, mental y social, además sus efectos sobre la salud pueden ser acumulativos, multiplicativos y se evidencian a largo plazo (2).…”
Section: Introductionunclassified
“…Lifestyles are a set of behavioral patterns that denote people's way of life, which is closely related to motivational and behavioral aspects (Espina-Romero, Guerrero-Alcedo & Marreros, 2023). Research has found that, as a lifestyle, frugality is a significant and independent predictor of adopting positive environmental behaviors (Kropfeld et al, 2018).…”
Section: Frugality Green Purchasing Intention and Behaviormentioning
confidence: 99%